Professional Development vis-a-vis Teaching Effectiveness of Public Secondary Mathematics Teachers - Mercado, Henry Alwayne Rebato; Cabuquin, Jomar Cobacha (FKIP Universitas Lampung, 2023)
Professional Development Vis-à-vis Teaching Effectiveness of Public Secondary Mathematics Teachers. Objectives: This study examined the relationship between professional development and students' perceptions of mathematics teachers' teaching effectiveness in one of the largest public high schools in Eastern Visayas, Philippines. Methods: Descriptive and correlational research designs were employed to address the study's objectives. The participants included 30 mathematics teachers and 314 randomly picked students from all the classes handled by the mathematics teachers. An adopted survey questionnaire collected the data on Teaching Effectiveness and Questionnaire Checklist. Findings: Results revealed a moderately significant positive relationship between teaching experience and participation in professional development activities, and mathematics teachers' commitment. The result suggests that commitment to the teaching profession necessitates teaching experience. The study likewise indicated a significant positive relationship between mathematics teachers' professional development activities and teaching for independent learning. Conclusion: Exposure to such professional activities is an essential factor that influences teachers' development, sense of responsibility to their profession, and ability to assist their students in becoming independent learners. School leaders should also encourage teachers' professional development to broaden their understanding of innovative teaching methods and practices appropriate for 21st-century education. Keywords: mathematics teachers, perceptions, personal development, profile, teaching effectiveness.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202332